Brominations with Pr4NBr9 as a Solid Reagent with High Reactivity and Selectivity - Beck, Thorsten M.; Haller, Heike; Streuff, Jan; Riedel, Sebastian (Synthesis, 2014)
Tetrapropylammonium nonabromide (Pr4NBr9) is introduced as a room-temperature solid reagent for rapid bromination reactions of various substrates. The reagent exhibits reactivity similar to that of elemental bromine, but shows higher selectivity and it is easier and safer to store and to handle.
Keywords: alkenes; arenes; bromine; halogenation; nonabromide